Interaction of a novel dihydropyridine K(+) channel opener, A-312110, with recombinant sulphonylurea receptors and K(ATP) channels: comparison with the cyanoguanidine P1075 - Felsch, Holger (2004)
1. ATP-sensitive K(+) channels (K(ATP) channels) are composed of pore-forming subunits (Kir6.x) and of regulatory subunits, the sulphonylurea receptors (SURx). Synthetic openers of K(ATP) channels form a chemically heterogeneous class of compounds that are of interest in several therapeutic areas. We have investigated the interaction of a novel dihydropyridine opener, A-312110 ((9R)-9-(4-fluoro-3-iodophenyl)-2,3,5,9-tetrahydro-4H-pyrano[3,4-b]thieno [2,3-e]pyridin-8(7H)-one-1,1-dioxide), with SURs and Kir6/SUR channels in comparison to the cyanoguanidine opener P1075. 2. In the presence of 1 mM MgATP, A-312110 bound to SUR2A (the SUR in cardiac and skeletal muscle) and to SUR2B (smooth muscle) with K(i) values of 14 and 18 nM; the corresponding values for P1075 were 16 and 9 nM, respectively. Decreasing the MgATP concentration reduced the affinity of A312110 binding to SUR2A significantly more than that to SUR2B; for P1075, the converse was true. At SUR1 (pancreatic β-cell), both openers showed little binding up to 100 μM. 3. In the presence of MgATP, both openers inhibited [(3)H]glibenclamide binding to the SUR2 subtypes in a biphasic manner. In the absence of MgATP, the high-affinity component of the inhibition curves was absent. 4. In inside-out patches, the two openers activated the Kir6.2/SUR2A and Kir6.2/SUR2B channels with similar potency (∼50 nM). Both were almost 2 × more efficacious in opening the Kir6.2/SUR2B than the Kir6.2/SUR2A channel. 5. The results show that the novel dihydropyridine A-312110 is a potent K(ATP) channel opener with binding and channel-opening properties similar to those of P1075.